ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PROSES PADA ROTI GULUNG DI UMKM KELANA BAKERY KABUPATEN MADIUN - Sindi Sri Utami; Amelia Putri, Della; Firos Dzulfikar, Muhammad; Putri Rejeki Hartono, S.E., M.Acc, Halleina (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the calculation of production costs using the process cost method on rolled bread products produced by Kelana Bakery UMKM in Madiun, East Java. This study uses a quantitative approach with a descriptive method through primary data collection from interviews and documentation. The results of the study indicate that the calculation of production costs carried out by Kelana Bakery is not in accordance with accounting standards, because it only includes the cost of raw materials and labor, without taking into account factory overhead costs. With the process cost method, all cost elements, including raw materials, labor, and factory overhead, are calculated in detail. The calculation of this method produces a more accurate production cost of Rp 579 per unit compared to Rp 520 per unit calculated by the company. The conclusion of this study shows that the use of the process cost method can provide a more accurate picture of the company's profit or loss. The suggestion given is for Kelana Bakery to adopt an appropriate cost accounting method to improve calculation accuracy and support better decision making.